Relationship between cardiovascular risk factors and the echogenicity and pattern of the carotid intima-media complex in men - Sarmento, Priscilla Lopes da Fonseca Abrantes (2014)
CONTEXT AND OBJECTIVE: The thickness of the carotid intima-media complex (C-IMC) is considered to be a marker of early atherosclerosis, but visual and echogenic changes to the C-IMC can also be noted. The objective here was to evaluate the relationship between cardiovascular risk factors and the echogenicity of the C-IMC and identify those most associated with an “abnormal” C-IMC. DESIGN AND SETTING: Cross-sectional study in the ultrasound sector of the Department of Diagnostic Imaging, Universidade Federal de São Paulo. METHODS: Eighty men were evaluated. Measurements of arterial blood pressure, waist circumference (WC), lipid profile, fasting glucose, uric acid and high-sensitivity C-reactive protein were obtained. The thickness of the C-IMC was measured by means of B-mode ultrasound, and the intima-media grayscale mean (IM-GSM) and standard deviation (IM-SD) were calculated. RESULTS: The following were discriminating variables: fasting glucose (r2 = 0.036; P = 0.013), uric acid (r2 = 0.08; P = 0.03), IM-SD (r2 = 0.43; P < 0.001), IM-GSM (r2 = 0.35; P < 0.001) and thickness of the C-IMC (r2 = 0.29; P < 0.001). IM-GSM showed significant correlations with WC (r = -0.22; P = 0.005), fasting glucose (r = -0.24; P = 0.002) and high-density lipoprotein cholesterol (HDL-C) (r = 0.27; P = 0.0007). CONCLUSION: IM-GSM showed correlations with WC, fasting glucose and HDL-C. However, uric acid and IM-SD presented the greatest discriminating impact. These results suggest that visual changes in C-IMC may help identify patients with potential cardiovascular risk, independently of the thickness of the C-IMC.